Atacamaptilia ambrosiavora gen. et sp. nov. (Lepidoptera: Gracillariidae), a leaf miner of Ambrosia cumanensis (Asteraceae) in the Atacama Desert - Espinoza-Donoso, Sebastián; Gonçalves, Gislene L.; Vargas, Héctor A.; Moreira, Gilson R. P. (Zootaxa, 2022)
Adult and immature stages of Atacamaptilia ambrosiavora Vargas & Espinoza-Donoso gen. et sp. nov. (Lepidoptera: Gracillariidae: Acrocercopinae) from the Atacama Desert of northern Chile are described and illustrated. The Neotropical Atacamaptilia Vargas & Espinoza-Donoso gen. nov. resembles the Old World genera Melanocercops Kumata & Kuroko, 1988 and Phodoryctis Kumata & Kuroko, 1988 in wing venation. However, differences in genitalia morphology enable the recognition of Atacamaptilia Vargas & Espinoza-Donoso gen. nov. as a different genus. COI sequences support this delimitation, since it is not closely phylogenetically related to these genera. A divergence of 18% (Kimura 2-parameter model) of A. ambrosiavora Vargas & Espinoza-Donoso gen. et sp. nov. to its nearest neighbor Leucospilapteryx omissella (Stainton, 1848) was found. The larvae of A. ambrosiavora Vargas & Espinoza-Donoso gen. et sp. nov. mine leaves of Ambrosia cumanensis Kunth (Asteraceae).